Medieval name and ethnicity: Serbs and Vlachs - Stareţu, Ştefan (Balcanica Posnaniensia. Acta et studia, 2015)
This article is aimed at showing the existence of a medieval aristocracy in north-eastern Hungary, characterized in connection to certain elements of the Serbian identity. The noble families from the Maramuresh region are often identified by their Orthodox identity. It linked them to the Serbian church organization and the Serbian aristocracy, in contrast with the peasants mostly represented by the Vlachs. The migration of the Vlachs within this zone probably was generated by the influx of noble elements from Serbia to Hungary, especially during the period, when Stefan Vladislav influenced actively the Hungarian politics in the 13-14th century. In this article I show, that the social and ethnic processes in the region were determined by a wider context of connections between Serbia and Hungary and the presence of the Serbian Orthodox church. The Catholic organization in Hungary accepted its autonomy and ecclesiastical independence. That is why there was possible to integrate the Orthodox elites to Hungarian nobility and arrange a kind of dual identity of the region. On the other side, in the long-term perspective, the Orthodox branches became rustic, living in villages with other nobles who became impoverished. Only of the Magyarized groups were able to remain within the high aristocracy.